Diagnosis and treatment of chronic cough in China: an insight into the status quo - Lai, Kefang (BioMed Central, 2012)
Chronic cough is a very common complaint in clinics throughout China. Clinical and basic science research on chronic cough started late, but in recent years the effort has yielded promising findings regarding the etiological diagnosis, treatment and pathogenesis. We found that inflammation in nonasthmatic eosinophilic bronchitis has some similarities to cough variant asthma but also a number of distinct differences. Recent evidence has also suggested a mechanistic link between airway neurogenic inflammation and and gastroesophageal reflux cough (GERC). Cough-related animal models have been developed, including models for esophageal reflux, nonasthmatic eosinophilic bronchitis and allergic rhinitis. Normal reference values for differential cell counts in induced sputum, cough sensitivity and esophageal 24-h pH monitoring in Chinese healthy subjects have been established. By using a modified algorithm for the etiological diagnosis of chronic cough, the causes of chronic cough have been investigated across a number of cities in China. The most common causes of chronic cough are cough variant asthma, eosinophilic bronchitis, upper airway cough symptoms, atopic cough and GERC, however, there are some regional variations. The Chinese National Guidelines on Diagnosis and Management of Chronic Cough were drafted in 2005, updated in 2009, and have been widely publicized and disseminated through many channels since their publication.